Analisis Pengaruh Likuiditas Struktur Modal dan Aktivitas Terhadap Profitabilitas pada PT Perusahaan Listrik Negara Pesero Tbk (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of Current Ratio (CR), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO) on Return on Assets (ROA) at PT Perusahaan Listrik Negara (Persero) Tbk for the period 2015–2024. The study uses a quantitative approach with an associative design. The data used are the company's annual financial reports obtained from the Indonesia Stock Exchange and PT PLN (Persero) Tbk. Data analysis was carried out using multiple linear regression supported by classical assumption tests, partial tests, simultaneous tests, and coefficients of determination with the help of IBM SPSS 25. The results of the study indicate that partially CR, DER, and TATO do not have a significant effect on ROA. Simultaneously, the three variables are also unable to explain changes in company profitability significantly. The coefficient of determination value indicates that variations in ROA can only be partially explained by CR, DER, and TATO, while the rest is influenced by other factors outside the research model. These findings indicate that the profitability of PT PLN (Persero) Tbk is more influenced by operational factors, management policies, and the company's external conditions than by aspects of liquidity, capital structure, and asset activity.